Analisis Faktor-Faktor Penentu Pertumbuhan Ekonomi Kabupaten Kota Provinsi Jawa Tengah Tahun 2010- 2019 - Mohammad Faizal; Ida Nuraini (Jurnal Ilmu Ekonomi, 2021)
This study aimed to analyze the effect of labor and capital expenditure on economic growth by using data from 35 regencies/cities in Central Java years of 2010-2019. The method was used multiple linear regression by panel data and hypothesis test. This study showed that the labor and capital expenditure variable is positively related and significant to economic growth in regencies/cities Centra Java. To summarize, the government was supposed to grow labor totals through education, training, and experience and add a job to reduce unemployment. The government was supposed to maximize capital expenditures to assist Central Java's facilities and infrastructure regencies/cities.